TTG‐Adakitic‐Like (Tonalitic‐Trondhjemitic) Magmas Resulting From Partial Melting of Metagabbro Under High‐Pressure Condition During Continental Collision in the North Qaidam UHP Terrane, Western China. Issue 3 (2nd March 2019) - Yu, Shengyao; Zhang, Jianxin; Li, Sanzhong; Santosh, M.; Li, Yunshuai; Liu, Yongjiang; Li, Xiyao; Peng, Yinbiao; Sun, Deyou; Wang, Zhengyi; Lv, Pei
Abstract: The tectonic regime and melting conditions of adakitic tonalitic‐trondhjemitic leucosomes and tonalite plutons from the North Qaidam terrane are evaluated through petrology, whole‐rock major, trace element and Sr‐Nd isotopic data and zircon U‐Pb data. Zircons from leucosomes and metabasites preserve distinct U‐Pb age populations: early Ordovician inherited zircon cores record a protolith age of 470 Ma, whereas zircon rims preserve subsequent HP granulite facies metamorphism, anatexis, and magmatism between 437 and 433 Ma. Whole‐rock geochemistry suggests that three types of leucosomes and tonalite plutons have geochemical features similar to adakites. Type 1 leucosomes record high Sr contents and positive Eu anomalies representing an earlier period of plagioclase accumulation. The flat fractionated rare earth element patterns of type 2 leucosomes correspond to residues of HP mafic granulites, and the steep fractionated rare earth element patterns of type 3 leucosomes correspond to garnet‐ and clinopyroxene‐rich residues. Petrological observations with P‐T paths and experimentally constrained melting curves together infer that melting of the metagabbro were triggered by the breakdown of amphibole ± zoisite under high‐pressure conditions. Therefore, tonalite, trondhjemite, and granodiorite (TTG)‐adakitic magmas in the North Qaidam terrane were produced through partial melting of newly emplaced gabbroic rocks with an arc affinity under high‐pressure, granulite facies conditions in a thickened lower crust during continental collision. This model explains the origin of TTG‐adakitic rocks and related continental growth and crustal differentiation genetically associated with continental collision. Key Points: TTG‐like magmas in the North Qaidam were produced by partial melting of newly emplaced metagabbros under HP granulite facies conditions Metagabbros possess a subduction‐related arc signature, whereas leucosomes and tonalite plutons record geochemical features similar to TTGs TTG‐like rocks and related continental growth genetically are associated with continental collision zones